THE EFFECT OF WOOLWICH MASSAGE THERAPY ON BREAST MILK PRODUCTION IN POSTPARTUM MOTHERS IN KEMIRI VILLAGE KEBAK KRAMAT - Choirunnisa Salsabila (JURNAL KEPERAWATAN, 2022)
Background: WHO and UNICEF recommend exclusive breastfeeding, namely the introduction of breast milk after the age of 6 months, without the addition and/or replacement of other foods. Exclusive breastfeeding coverage in Indonesia is 66.06%, Central Java 81.4% and Karanganyar 69%. Health services Psychological and socio-cultural factors can lead to several breastfeeding problems, including insufficient milk production. One of the supportive interventions is Woolwich Massage Therapy, which is a form of therapy to increase milk production. Objective: To determine the effect of Woolwich Massage Therapy on breast milk production in postpartum mothers in Kemiri Village, Kebak Kramat. Methods: This type of research is quantitative, this research method uses Pre-experimental Design with One Group Pre-Test-Post Test Design. Sampling of 20 respondents. The research instrument used a breast milk production questionnaire. Data analysis with Wilcoxon test. Results: The results showed a significant value of Woolwich Massage Therapy on breast milk production with a p-value of 0.000 <0.05. Conclusion: There is a significant effect of Woolwich Massage Therapy on breast milk production in postpartum mothers in Kemiri Kebak Kramat Village.